Business Density, Financial Development and Carbon Footprints: Examining the Energy-Sustainability Trade-off in East Asia and the Pacific - Osabohien, Romanus; Jaaffar, Amar Hisham; Kimpah, Jeniboy; Al-Faryan, Mamdouh Abdulaziz Saleh (International Journal of Energy Economics and Policy, 2025)
This study investigates the relationship between business density, financial development, and their potential trade-off with carbon footprints in the world’s largest continent. Rapid economic growth and industrialization in Asia have led to concerns about its environmental impact, particularly with regards to carbon emissions and sustainable development. By analysing data from various countries in East Asia and the Pacific, this study aims to shed light on the intricate relationship between business density, financial development, and the trade-off between carbon footprints and sustainable development. The study utilizes a panel dataset covering multiple countries in East Asia and Pacific, allowing for a comprehensive analysis of the economic, financial, and environmental dimensions Carbon footprints are assessed based on carbon emissions, energy consumption, and environmental sustainability indices. Findings suggest a positive correlation between business density and financial development, indicating that countries with higher business density tend to experience greater financial growth. However, this growth often comes at the expense of increased carbon footprints, as reflected in higher carbon emissions and energy consumption. These findings highlight a potential trade-off between economic development and environmental sustainability in the context of Asia. The research contributes to the existing literature on the nexus between business density, financial development, and sustainability in Asia. It provides valuable insights for policymakers, businesses, and environmentalists to better understand the challenges and opportunities associated with balancing economic growth and environmental conservation in the region.